Effects of Preconditioning and Temperature During Germination of 73 Natural Accessions of Arabidopsis thaliana - SCHMUTHS, HEIKE (Oxford University Press, 2006)
• Background and Aims Germination and establishment of seeds are complex traits affected by a wide range of internal and external influences. The effects of parental temperature preconditioning and temperature during germination on germination and establishment of Arabidopsis thaliana were examined. • Methods Seeds from parental plants grown at 14 and at 22 °C were screened for germination (protrusion of radicle) and establishment (greening of cotyledons) at three different temperatures (10, 18 and 26 °C). Seventy-three accessions from across the entire distribution range of A. thaliana were included. • Key Results Multifactorial analyses of variances revealed significant differences in the effects of genotypes, preconditioning, temperature treatment, and their interactions on duration of germination and establishment. Reaction norms showed an enormous range of plasticity among the preconditioning and different germination temperatures. Correlations of percentage total germination and establishment after 38 d with the geographical origin of accessions were only significant for 14 °C preconditioning but not for 22 °C preconditioning. Correlations with temperature and precipitation on the origin of the accessions were mainly found at the lower germination temperatures (10 and 18 °C) and were absent at higher germination temperatures (26 °C). • Conclusions Overall, the data show huge variation of germination and establishment among natural accessions of A. thaliana and might serve as a valuable source for further germination and plasticity studies.